p53 enhances elesclomol-Cu-induced cuproptosis in hepatocellular carcinoma via FDXR-mediated FDX1 upregulation - Liu, Xiao; Qu, Honglin; Li, Jingmin; Sun, Xuhong; Wang, Zhenlin; Wang, Dong; Bai, Xianyong; Li, Xiaoyan (Frontiers in Oncology, 2025)
BackgroundCuproptosis, a novel cell death pathway mediated by ferredoxin 1 (FDX1) and protein lipoylation, has emerged as a valuable target in cancer therapy. Although the findings of previous research have indicated a potential correlation between p53 and cuproptosis, the precise role and underlying mechanisms of p53 in cuproptosis, particularly within the context of hepatocellular carcinoma (HCC), remain unclear.MethodsTo evaluate cuproptosis, three HCC cell lines (HepG2, PLC/PRF/5, and Hep3B2.1-7) with distinct p53 statuses were treated with elesclomol-Cu. p53 overexpression/knockdown, siRNA-mediated ferredoxin reductase (FDXR)/FDX1 knockdown, and the p53 activators CP-31398 and nutlin-3 were employed to elucidate the associated molecular mechanisms. Cell viability, protein expression [FDX1, dihydrolipoyl transacetylase (DLAT), FDXR], and DLAT oligomerization were assessed via Cell Counting Kit-8 (CCK-8), western blotting, and immunofluorescence analyses. A PLC/PRF/5 xenograft mouse model was used to assess combined the therapeutic efficacy of elesclomol-Cu and CP-31398.ResultsElesclomol-Cu triggered cuproptosis in HCC cells, as evidenced by a dose-dependent suppression of proliferation, FDX1 upregulation, DLAT oligomerization, and rescue by the copper chelator tetrathiomolybdate (TTM). p53 activation enhanced FDXR expression, promoting FDX1 upregulation and subsequent DLAT oligomerization, thereby sensitizing HCC cells to elesclomol-Cu, whereas FDXR knockdown reversed these effects, demonstrating its role in p53-mediated potentiation of cuproptosis sensitivity. In mutant p53-R249S cells, CP-31398 functioned synergistically with elesclomol-Cu to suppress proliferation. In vivo, elesclomol-Cu and CP-31398 combination therapy significantly reduced tumor growth and Ki67 expression whilst upregulating FDXR levels.ConclusionsThese findings revealed that p53 enhances elesclomol-Cu-induced cuproptosis in HCC via FDXR-mediated FDX1 upregulation. This study provides mechanistic insights into p53’s role in cuproptosis and may serve as a basis for targeting copper metabolism in therapeutic strategies for HCC.